Rozwiązane

PROSZĘ O POMOC !
DAJE NAJ!



PROSZĘ O POMOC DAJE NAJ class=

Odpowiedź :

Odpowiedź:

a) -2 * (2y+5b) - 3 * (2y+3b) = - 4y - 10b - 6y - 9b = -4y - 6y - 10b - 9b = -10y - 19b

b) 5 * (a-2c) + 2 * (6c - 2a) = 5a - 10c + 12c - 4a = 5a - 4a - 10c + 12c = 1a + 2c

c) 4 * (x - 2) +3 * (5+ 3x) - 4 = 4x - 8 + 15 + 9x = 4x + 9x - 8 + 15 = 13x + 7

d) -2 * (2a +3b) - 2 * (3b - 2a) = -4a - 6b -6b +4a = -4a + 4a -6b -6b = -12b

e) 2 * (x + 3) +2 * (3z - x) + (-2z + 8x) = 2x + 6 + 6z - 2x + 2z - 8x = 8z + 6 - 10x

f) -5 * (1,6c - 4a) - 2 * (2c + 2a) = -8c + 20a -4c -4a = 16a - 12c

g) -3 * (4x + 2y) - 3 * (2x - 3y) = -12x - 6y -6x - 9y = -18x - 15y

h) -4 * (3z + 2t) + 5 * (2,4z - 3,4t) = -12z - 8t + 12z - 17t = - 25z

i) -2 * (3,2c - 3,5b) + 2 * (2,5c - 2,3b) = - 6,4c + 7b + 5c - 4,6b = -1,4c + 2,4b

j) -4 * (3 + 5x) - 3 * (y + 4x) - (4x + 8y) =  - 12 - 20x -3y - 12x - 4x - 8y= -12-36x -11y

k) -2 * (3,2z - 4) - 2 * (5-2,3z) + 1,5t = -6,4z + 8 -10 + 4,6z + 1,5t = -2 - 1,8z + 1,5t

l) -2 * (2x - a ) - 4 * (2x - 3a) = -4x + 2a -8x + 12a = 14a - 12x

m) -3 * (4x - 5d) + 2 * (4d - 3x) = -12x + 15d +8d - 6x = -18x + 23d

n) -4 * (2,6x + 4a) - 3 * (4x - 1,6a) = -10,4x - 16a - 12x + 4,8a = -11,2a- 22,4x

o) 3 * (3a - 1,3k) + 2 * (-2,2k - 3a) = 9a - 3,9k -4,4k - 6a = 3a - 8,3k

p) -2 * (3,6x - 4,2a) - 3 * (1,7x + 3a) = -7,2x + 8,4a - 5,1x - 9a = -0,6a - 12,3x

q) -3 * ( 2,3x - 2,7a) +3 * (2a - 1,4x) = -6,9x + 8,1a + 6a -4,2x = 14,1a - 11,1x

r)  j) - 5 * (3 + 2x) + 2 * (4,3 - 2x ) = j -15 - 10x + 8,6 - 4x = -6,4 - 14x + j

s) k) - 3 * (4k - 5x) + 2 * (2x - 3k) = k - 12k + 15x + 4x - 6k = 17k + 19x

Krótkie wyjaśnienie:

a) -2 * (2y+5b) - 3 * (2y+3b) = -2 * 2 y - 2 *5b - 3 *2y - 3 * 3b = -4y - 10b - 6y - 9b = -10y - 19b

Itd. z kolejnymi działaniami

Inne Pytanie